SECONDARY SCHOOL STUDENTS’ APTITUDE IN SCIENCE - A STUDY - Bhargavi, T. R.; Renuka, P. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Aptitude represents a learner’s cognitive readiness to acquire knowledge and apply reasoning skills in academic contexts. The present investigation examines aptitude levels among secondary school students with specific reference to gender and selected socio-demographic variables. A balanced sample of 100 students (50 boys and 50 girls) was drawn from different schools representing rural and urban localities, government and private management, various mediums of instruction, parental educational qualifications, parental professional status, and economic background. Descriptive statistics and an independent samples t-test were employed. The overall aptitude mean was 41.82 (SD = 6.04). Boys recorded a mean of 41.35 (SD = 6.52), while girls obtained 42.29 (SD = 5.51). The calculated value, t(98) = 0.78, p> .05, indicated no statistically significant gender difference. However, observable variations emerged across socio-economic and parental educational categories. The findings underscore the influence of social capital on aptitude development and highlight the necessity of inclusive educational strategies.